(untitled) (Nigerian Journal of Technology, 2024)
This paper provides a method of assessing the toughness of augmented cables required for Ethernet technology. The use of augmented category 6 (Cat 6A) in Ethernet-enabled Internet of Things (IoT) infrastructure continues to grow due to the high demand for services requiring such configuration. The increasing demand for Cat 6A over Ethernet is due to its ability to transmit both data and power to devices used in IoT which is cost-saving. However, the availability of counterfeit and substandard cables in the market disguised as category-rated cables is of great concern to cable installers and engineers. There is also the basic problem of handling stress anticipated during installation as cables could be manipulated in the form of repeated coiling and uncoiling. Therefore, there is a need to have a method of assessing the toughness of the cables before deployment. In this paper, two Cat 6A cables from different manufacturers were selected from the market to be used as samples for the experiment. The Cat 6A cables were exposed to two rounds of coiling to imitate the handling stress anticipated during installation. The return loss and near-end crosstalk (NEXT) of the cables which are the major performance indicators were collected using the DSX-5000 cable analyzer for each of the test processes. This is to evaluate their resilience or otherwise to handling stress. Feature Selective Validation (FSV) which is a standardized method of measuring the degree of agreement between two data sets was used in this research. The results showed the cable with the lowest variations between the first and third test measurements for each of the pairs examined. The method presented showed that it can be used to assess cable measurements which can lead to objective decisions on the cables selected for deployment.